Adaptation of VegSyst-DSS for N, P and K recommendations for grafted tomato grown in perlite in Mediterranean greenhouses - M. Gallardo; J.M. Cedeño; J.J. Magán; M.D. Fernández; R.B. Thompson (Agricultural Water Management)
Substrate is commonly used for greenhouse vegetable production in the Mediterranean regions of the EU and Türkiye. These are mostly free-draining systems in which drainage enters underlying soil. These systems are generally very contaminating. Unlike substrate-growing systems with recirculation of drainage, very few tools and strategies have been developed to optimize nutrient management for free-draining substrate. The VegSyst-DSS V2 and its component VegSyst V3 simulation model were both adapted to provide recommended N, P and K concentrations for nutrient solution (NS) applied to tomato in free-draining perlite substrate. Firstly, the VegSyst model calibration for tomato, developed for non-grafted plants, was adapted to grafted plants. The recalibrated model was then used to simulate N, P and K uptake in crop dry matter. The apparent nutrient retention in or loss from perlite was calculated. Using these data, the VegSyst model V3 simulated nutrient uptake by the cropping system (i.e., in dry matter plus the apparent retention in/loss from substrate). These values were then used to simulate nutrient uptake concentrations for the growing system. These latter values were used with the mass balance equation of Sonneveld (2000), in the adapted VegSyst-DSS V2, to calculate the recommended concentrations of N, P and K in the applied NS. This work was conducted in the context of a Long Cycle (early autumn to late spring) and a Spring Cycle of grafted tomato crop grown in free-draining perlite, each with a conventional (CT) and optimized nutrient management treatment (OT) (which was based on ratios of nutrient concentrations in drainage and NS). The Long Cycle CT was used for calibration, the other three crops for validation. A suite of statistical indices indicated generally good performance of simulation of nutrient uptake in crop dry matter and by the cropping system, and of crop uptake concentration for N, P and K. The recommended NS concentrations calculated by the adapted VegSyst-DSS V2 were very similar to those of the OT treatments in Long Cycle and Spring crops. Scenario analyses demonstrated how perlite age affected recommended NS concentrations through differential nutrient retention in/loss from perlite substrate.